Engrailed cooperates with extradenticle and homothorax to repress target genes in Drosophila. - Kobayashi, M.; Fujioka, M.; Tolkunova, E.N.; Deka, D.; Abu-Shaar, M.; Mann, R.S.; Jaynes, J.B. (Development, 2003)
Engrailed is a key transcriptional regulator in the nervous system and in the maintenance of developmental boundaries in Drosophila, and its vertebrate homologs regulate brain and limb development. Here, we show that the functions of both of the Hox cofactors Extradenticle and Homothorax play essential roles in repression by Engrailed. Mutations that remove either of them abrogate the ability of Engrailed to repress its target genes in embryos, both cofactors interact directly with Engrailed, and both stimulate repression by Engrailed in cultured cells. We suggest a model in which Engrailed, Extradenticle and Homothorax function as a complex to repress Engrailed target genes. These studies expand the functional requirements for extradenticle and homothorax beyond the Hox proteins to a larger family of non-Hox homeodomain proteins.